2017
DOI: 10.1155/2017/9460190
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications of Oscillatory Lung Function during Methacholine Bronchoprovocation Testing of Preschool Children

Abstract: Objective To investigate the repeatability and safety of measuring impulse oscillation system (IOS) parameters and the point of wheezing during bronchoprovocation testing of preschool children. Methods Two sets of methacholine challenge were conducted in 36 asthma children. The test was discontinued if there was a significant change in reactance (Xrs5) and resistance (Rrs5) at 5 Hz (Condition 1) or respiratory distress due to airway obstruction (Condition 2). The repeatability of PC80_Xrs5, PC30_Rrs5, and whee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Such cut-offs could have better clinical utility than spirometry-based tests. Airway hyperresponsiveness measured by oscillometry is reproducible [28,30,41,143] and is correlated with responsiveness measured by forced expiratory volume in 1 s (FEV 1 ).…”
Section: Bronchial Challenge Testingmentioning
confidence: 94%
“…Such cut-offs could have better clinical utility than spirometry-based tests. Airway hyperresponsiveness measured by oscillometry is reproducible [28,30,41,143] and is correlated with responsiveness measured by forced expiratory volume in 1 s (FEV 1 ).…”
Section: Bronchial Challenge Testingmentioning
confidence: 94%
“…AHR detected by oscillometry is repeatable [47,49,61,72] and correlates with responsiveness based on FEV 1 [73], but the correlations of spirometry and oscillometry are inconsistent. There is wide variability across studies, which may be explained by differences in methodology and study populations.…”
Section: Bronchial Challenge Testingmentioning
confidence: 99%
“…Bronchial hyper-responsiveness studies comparing FOT with different lung function measures have reported FOT to be as effective as spirometry[ 63 - 69 ] and as sensitive as body plethysmography[ 70 ] and transcutaneous PO 2 [ 50 ] in older children with asthma. BHR has been assessed using FOT in children younger than 7 years of age with a range of challenge tests including adenosine monophosphate (AMP)[ 19 ], cold air[ 24 ], normal saline[ 21 ] methacholine[ 22 , 62 , 63 , 66 , 68 , 71 ], mannitol[ 25 ] and exercise[ 20 , 72 ] demonstrating that FOT can be reliably used in young children for challenge testing.…”
Section: Introductionmentioning
confidence: 99%